ANALISA SISTEM INFORMASI ALIH MEDIA REKAM MEDIS BERBASIS WEB DENGAN METODE PIECES DI RSUD DR. R. SOEDARSONO KOTA PASURUAN - Alif Faiz Risqullah; Ulya Anisatur Rosyidah; Mohammad Dasuki (Lafadz Jaya Publisher, 2023)
Medical records are one part of the hospital that plays an important role in running the Hospital Information System (SIRS). The Medical Record Media Transfer System is a web-based application used to convert printed files into pdfs. This study aims to evaluate the application of medical record media transfer using the PIECES method. This research was evaluated with several PIECES factors, namely Performance, Information, Economy, Control and Security, Effeciency, and Service. The use of the PIECES method can discover how feasible a medical record media transfer application is to be used. The results of this study were in the form of testing from 10 samples using questionnaires and producing good category values. The medical record media transfer application can be declared suitable for use at Dr. R. Soedarsono Hospital, Pasuruan City.